1988
DOI: 10.1086/132343
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance Gradient in NGC 3344

Abstract: The steep abundance gradient found by McCall, Shields, and Rybski (1981) in the Sbc galaxy NGC 3344 is confirmed by a measurement of the electron temperature in the outer H II region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The plot with [N II]/Hα has less scatter and a higher probability, and may therefore suggests a higher metallicity for the SNRs near the galaxy centre. This result is agreement with the strong abundance gradient for H I regions found by(McCall et al 1981) and confirmed by(Vilchez et al 1988).…”
supporting
confidence: 92%
“…The plot with [N II]/Hα has less scatter and a higher probability, and may therefore suggests a higher metallicity for the SNRs near the galaxy centre. This result is agreement with the strong abundance gradient for H I regions found by(McCall et al 1981) and confirmed by(Vilchez et al 1988).…”
supporting
confidence: 92%
“…The adopted properties of our galaxies. NGC 0598 (M 33) Smith (1975), Kwitter & Aller (1981), McCall et al (1985, Díaz et al (1987), Vílchez et al (1988b), Bresolin et al (1999) NGC 5457 (M 101) Smith (1975), Hawley (1978), Sedwick & Aller (1981), Rayo et al (1982), Skillman (1985), McCall et al (1985), Torres-Peimbert et al (1989), Kinkel & Rosa (1994), Garnett & Kennicutt (1994), Kennicutt & Garnett (1996) NGC 7793 Webster & Smith (1983), ), McCall et al (1985, Bibby & Crowther (2010) IC 0010 Lequeux et al (1979)…”
Section: Discussionmentioning
confidence: 99%